PENINGKATAN HASIL BELAJAR SISWA KELAS III MELALUI MEDIA DIORAMA METAMORFOSIS SDN WONOKUSUMO IV/43 SURABAYA - Fiy Afnanin, Nora; Hendratno; Hanafia, Adika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to improve the learning outcomes of students in grade III of SDN Wonokusumo IV/43 Surabaya on the metamorphosis of living things. This Classroom Action Research (CAR) used qualitative and quantitative approaches. This study was conducted for three cycles, namely pre-cycle, cycle 1 and cycle 2. Data collection techniques used observation, interviews with teachers, observations during learning and final evaluation for students based on the results of the pre-test and post-test. The results of the study showed that the use of diorama media can significantly improve the understanding and learning outcomes of Natural and Social Sciences metamorphosis material. Students not only showed understanding and improved learning outcomes but also increased involvement and motivation to learn. The results of observations in the pre-cycle were 56,92%, the results of observations in cycle 1 showed that 67.69% and the results of observations in cycle II showed that 82.69% of students experienced an increase. Based on the results of the study, diorama media can provide benefits to improve student learning outcomes in the subject of Natural and Social Sciences.Top of FormBottom of Form